Histomorphological pattern of thyroid lesions: A prospective study - Shruthi Shruthi; Praveen Kumar Ram Bhat; Parvathi S. Jigalur (Al Ameen Medical College, 2022)
Background: Thyroid disorders are the commonest endocrine disorders worldwide. 15-20% of the thyroid nodules are indeterminate on cytological results. The definite diagnosis of these nodules is provided by examination of thyroidectomy. Objective: Aim was to describe various histomorphological patterns of thyroid lesions and their frequency in relation to age and sex of the patients. Material and methods: A prospective cross-sectional study was carried out on all thyroidectomy specimens received in the department of Pathology from July 2015 to June 2017. A total of 110 specimens were included in the study. Statistical analysis: Statistical analysis was carried out using SPSS (version 14) software. Descriptive analysis was performed using frequencies and percentages. Results: Thyroid diseases were predominantly seen in females. Peak age of presentation was 3rd to 5th decade. Out of 110 cases studied, 77 cases (70%) were non neoplastic lesions and 33 cases were (30%) neoplastic lesions. Adenomatous goiter was the most common nonneoplastic lesion (84.41%) followed by Hashimoto thyroiditis (11.68%). Among neoplastic lesions, malignant neoplasms (23 cases, 69.69%) were more common than benign neoplasm (9 cases, 27.27%). Borderline neoplasm was seen in 3.03% (1 case). Papillary carcinoma was the most common malignant neoplasm (78.26%), which was predominantly seen in females (94.44%) and most common age of presentation was in 3rd to 4th decade (66.66%). Overall, the most common lesion was adenomatous goiter (59.09%) followed by papillary carcinoma (16.36%), Hashimoto's thyroiditis (8.18%) and follicular adenoma (7.27%). Conclusion: Histopathological examination plays a major role in definitive diagnosis of thyroid lesions. Adenomatous goiter was the most common lesion followed by Papillary carcinoma which suggests increasing prevalence of thyroid malignancy in the population.